Erratum to: Discolouration of polyamide microcrystalline denture base plates after exposure to filter cigarette smoke [Padjadjaran Journal of Dentistry. 2019;31(2):112-116.] - Jubhari, Eri Hendra; Dangkeng, Zulkarnain Wahid; Dangkeng, Effendy (Padjadjaran Journal of Dentistry, 2020)
Erratum to the article entitled: Jubhari EH, Dangkeng ZW, Dangkeng E. Discolouration of polyamide microcrystalline denture base plates after exposure to filter cigarette smoke. Padjadjaran J Dent. 2019;31(2):112-116. DOI: 10.24198/pjd.vol31no2.15531 In Figure 1, previously, the Figure caption was written in Indonesian, which was “Gambar 1.A. Sampel dari bahan polyamide microcrystalline; B. Alat simulasi untuk mengisap dan menghembuskan asap rokok (Dokumentasi pribadi)”; has been translated into English to follow the journal language and grammatical consistency. Therefore, the caption is corrected to: “Figure 1.A. Samples from microcrystalline polyamide materials; B. Simulation device for smoking and exhaling cigarette smoke (Personal documentation)” Originally published: 31st July 2019; Corrected: 16th June, 2020 Previously cited as:Jubhari EH, Dangkeng ZW, Dangkeng E. Discolouration of polyamide microcrystalline denture base plates after exposure to filter cigarette smoke. Padjadjaran J Dent. 2019;31(2):112-116. DOI: 10.24198/pjd.vol31no2.15531 Now cited as:Jubhari EH, Dangkeng ZW, Dangkeng E. Erratum to: Discolouration of polyamide microcrystalline denture base plates after exposure to filter cigarette smoke [Padjadjaran Journal of Dentistry. 2019;31(2):112-116.] Padjadjaran J Dent. 2020;32(2):1-5. DOI: 10.24198/pjd.vol32no2.28451